Transfer matrix algorithm: Energy eigenvalue calculation of an arbitrary potential profile (Patan Pragya, 2022)
The main objective of this article is to study transfer matrix algorithm, energy eigenvalue calculation. This article gives the idea that, in quantum mechanics, the transfer matrix algorithmic a method for calculating the energy eigenvalues of an arbitrary potential profile. The algorithm is based on the transfer formalism, which expresses the wave function of a particle in a potential as a product of matrices. The transfer matrix algorithm is particularly well suited for potentials that are piecewise constant, such as the potentials often used in quantum dot and quantum well devices. The transfer matrix algorithm begins with the construction of the transfer.